TV Show Amateur Subtitling: the Case of Friends (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2020)
Thanks to the Internet we can access the so-called amateur subtitling. The main advantage of this phenomenon is, without a doubt, the free access to audiovisual content in our mother tongue, while one of its disadvantages is not knowing the source's origin. Most of these translations are anonymous, and therefore, the quality of the translation is questionable. This paper aims to investigate the quality of amateur translation online, as well as to research whether it respects the rules of audiovisual translation. To reach a conclusion in this regard, the work analyzes the quality of two such translations of the episode “The One with All Thanksgivings” of the American series Friends, found on the podnapisi.com website. Through a comparative analysis between the two translations and applying the theories of audiovisual translation, both the veracity and the formal aspects are studied. As a final objective of this study we want to show that the opposite cases can be found on the Internet, that is, both translations that do respect the translation rules as well as those that do not, and that there is no adequate or predefined strategy on how to find a reliable amateur audiovisual translation and of good quality.Keywords: translation, amateur subtitling, online, Internet, Friends.